Food insecurity on the college campus - Mark Lapping (Journal of Agriculture, Food Systems, and Community Development, 2022)
It is often said that one’s college years are “the best years of your life.” For a growing number of students facing food insecurity, these years may be anything but. These two very different books provide useful counterpoints on campus food insecurity, a growing phenomenon only made worse by the COVID-19 pandemic. Henry’s volume uses an ethnographic approach of interviewing over 90 students who use the food pantry at her university, the University of North Texas, Denton. Broton and Cady focus on essays and case studies of what a number of institutions are doing to address the issue of campus food insecurity. Together they provide both a balanced treatment of the subject and some remarkably interesting insights and strategies that other college communities can utilize. . . .